Issues in Intergovernmental Fiscal Relations in China - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2005)
The paper reviews the changing nature of intergovernmental fiscal relations between the provinces and the central government in China over the past two decades and provides an assessment of the success of previous reforms in meeting their objectives. Key existing weaknesses in the current system that undermine these objectives are identified. Alternative instruments, procedures, rules, and incentives that could result in better outcomes are outlined by drawing upon relevant cross-country experiences.